2016
DOI: 10.1016/j.socscimed.2016.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Medical mistrust among social network members may contribute to antiretroviral treatment nonadherence in African Americans living with HIV

Abstract: Rationale African Americans living with HIV are less likely to adhere to antiretroviral treatment (ART) compared to other racial/ethnic groups. Medical mistrust is thought to be a factor in this disparity. Objective We examined (1) whether exposure to HIV conspiracy beliefs, a specific type of HIV-related mistrust (about the origins and treatment of HIV) in social networks is associated with ART nonadherence among African Americans living with HIV; and (2) the characteristics of individuals who discuss HIV-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…Institutional or systemic racism creates an environment in which many African Americans have reduced access to housing, poorer neighborhood quality, lower educational quality and attainment, fewer employment options, and harsher incarceration sentences, all of which can negatively impact health behaviors. Notably, Bogart et al (2016) found that having a history of incarceration and being unemployed were both associated with lower adherence to ART. Cultural racism, evident in the maintenance of negative stereotypes about African Americans, as well as individuals’ experiences of racial discrimination can also have deleterious effects on mental health and health behaviors (Corral & Landrine, 2012; Williams, Neighbors, & Jackson, 2003; Williams & Mohammed, 2013).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Institutional or systemic racism creates an environment in which many African Americans have reduced access to housing, poorer neighborhood quality, lower educational quality and attainment, fewer employment options, and harsher incarceration sentences, all of which can negatively impact health behaviors. Notably, Bogart et al (2016) found that having a history of incarceration and being unemployed were both associated with lower adherence to ART. Cultural racism, evident in the maintenance of negative stereotypes about African Americans, as well as individuals’ experiences of racial discrimination can also have deleterious effects on mental health and health behaviors (Corral & Landrine, 2012; Williams, Neighbors, & Jackson, 2003; Williams & Mohammed, 2013).…”
mentioning
confidence: 97%
“…To this end, Bogart et al (2016), in this issue, present an analysis of one potential source of disparate engagement in treatment - medical mistrust of social network members- among African Americans living with HIV.…”
mentioning
confidence: 99%
See 3 more Smart Citations